Translation and history a textbook - Hermans, Theo 1948- (Routledge, 2022)
"This concise and accessible textbook is a comprehensive introduction to the key historical aspects of translation. Six chapters cover essential concepts in researching and writing the history of translation and translation as history. Theo Hermans presents and explains fundamental issues and questions in a clear and lively style. He includes numerous examples and case studies, and offers suggestions for further reading. Four of the six chapters take their cue from ideas about historiography that are alive among professional historians. They pay attention to the role of narrative, to the emergence of transnational, transcultural, global and entangled history, and to particular fields like the history of concepts and memory studies. Other topics include microhistory, Actor-Network Theory and book history. With an emphasis on methodology, how to do research in translation history and how to write it up, this is an essential text for all courses on translation history and will be of interest to anyone working in translation theory and methodology"--
Keywords: Geschichte; Übersetzung; Translating and interpreting / History; Translating and interpreting / History / Research / Methodology; Translating and interpreting; Translating and interpreting / Research / Methodology; History; Textbooks; Lehrbuch